Staff Nurses' Perception of the Hemodialysis Unit as Practice Environment and Patients' Perception of Nurse Caring Behaviors and their Level of Satisfaction - Jenel Koon (San Beda University, 2020)
Background: Despite the concomitant rise of kidney diseases and hemodialysis services nationwide, the Philippines still lacks research on hemodialysis nursing care quality. Using nursing-sensitive indicators under the Nursing Role Effectiveness Model, this study aimed to describe hemodialysis nurses' perception of their unit as practice environment; patients' perception of nurse caring behaviors based on Jean Watson's 10 Caritas Processes; patients' level of satisfaction on nursing care; and determine the association between perceived nurse caring behaviors and satisfaction levels. Methodology: This descriptive cross-sectional study purposely selected seven free-standing hemodialysis centers in Metro Manila. Ninety-four nurses were surveyed via complete enumeration using the Practice Environment Scale of Nursing Work Index (PES-NWI) while 345 randomly selected patients answered the Caring Factor Survey-Tagalog (CFS-T) and Patient Satisfaction of Nursing Care Quality Questionnaire-Tagalog (PSNCQQ-T). Pearson's correlation was used to analyze the gathered data. Results: The study revealed that nurses perceived their respective work unit as a favorable practice environment while hemodialysis patients perceived nurse caring behaviors as practiced to a great extent and their satisfaction with nursing care as very good. The study also revealed a significant positive correlation between the process and outcome indicators (r=0.64, p=<0.0001). Conclusion: The study reflected positive nursing-sensitive indicators in hemodialysis. However, hemodi alysis facilities should improve nurse staffing, spiritual nurse caring behavior, and facilitate a more healing environment while maintaining their current favorable qualities.